Contribuição ao estudo comparativo da genitália externa em sub-famílias de Reduviidae (Hemiptera-Heteroptera) - Jurberg, José (1978)
Five representatives of the Reduviid sub-families (Microtominae, Piratinae, Ectrichodiinae, Reduvinae and Triatominae), were studied with special reference to the morphology of the male and female genitalia. Drawings were made of the Terminalia from various angles (dorsal, ventral and lateral) to facilitate future studies on comparative morphology and to show the structural modifications present in the material studied. These detailed descriptions are based on the Terminology proposed by DUPUIS (1955). Selected references on previous morphological descriptions of genitalia are given as guide to future works on the group.